A pay-it-forward approach to improve feedback rate of HPV-based self-sampling in cervical cancer screening among women in ethnic minority regions of China: a randomized controlled trial protocol - Zhou, Xueyuan; Bao, Rantong; Guan, Xin; Li, Wenzhuo; Yang, Chenxin; Zhu, Ruijin; Li, Hui; Wang, Xiaohua (Frontiers in Psychiatry, 2025)
BackgroundHuman papillomavirus (HPV) infection is the primary cause of cervical cancer, and HPV self-sampling has emerged as a novel screening method with the potential to increase screening coverage and early detection of cervical cancer. However, the implementation of HPV self-sampling in China faces several challenges, including sociocultural factors, economic burdens, and low feedback rates. This study will aim to improve the feedback rate of HPV self-sampling results through a Pay-It-Forward approach and explore its impact on HPV positivity rates and subsequent treatment compliance.MethodsThis study employs a randomized controlled trial (RCT) design, enrolling women aged 24 and older who have not received the HPV vaccine and have not undergone HPV self-sampling or cervical cancer screening in the past 12 months. Participants will be randomly divided into a control group (free distribution of HPV self-sampling kits) and an intervention group (pay up front for HPV self-sampling). The prepayment amount is 20 RMB, which is fully refunded upon completion of the self-sampling and feedback of results. The primary outcome measure is the feedback rate of HPV self-sampling results. The study is conducted at maternal and child health care and family planning service centers in Hohhot, Inner Mongolia Autonomous Region, with an expected enrollment of 108 participants.DiscussionThe Pay-It-Forward approach is expected to significantly improve the feedback rate of HPV self-sampling results by enhancing participants’ psychological commitment and sense of responsibility. Additionally, this strategy may positively affect HPV positivity rates and subsequent treatment compliance. The innovation of this study lies in the first application of the Pay-It-Forward method to HPV self-sampling and the comprehensive analysis of urban-rural differences. The results of this study will provide a scientific basis for improving women’s cervical health awareness and optimizing HPV self-sampling intervention strategies, thereby promoting the widespread application of HPV self-sampling in cervical cancer screening.Trial registrationThis study registered at ClinicalTrials.gov (ChiCTR2500095770) on January 13, 2025.